Feedback and Feed-Forward for Promoting Problem-Based Learning in Online Learning Environments (Malaysian Journal of Learning and Instruction, 2016)
Purpose â€“ The study aimed to (1) review the literature to construct conceptual models that could guide instructional designers in developing problem/project-based learning environments while applying effective feedback strategies, (2) use the models to design, develop, and implement an online graduate course, and (3) assess the efficiency of the models. Method â€“ Quantitative and qualitative data were gathered during the implementation of an online graduate-level course that was designed and developed using the two proposed conceptual models. Eleven students were enrolled in the course. Multiple sources of data and analytical strategies were used to collect, analyze, and interpret the data. Findings â€“ The results show that the characteristics and strategies suggested in the proposed models supported student achievement in course projects and activities. The timely and frequent feedback allowed students to make necessary changes to their final project parts and improve performance. The motivating, informative/ specific feedback and feed-forward goals appeared to provide a reference for areas of student improvement. A balance of the three types of feedback, along with metacognitive questioning, supported student improvement. Because the frequency of feedback was dependent upon student request, those who needed more frequent feedback during the acquisition of learning benefited from that, but those who did not need it received the moderate amount necessary to be successful. Significance â€“ The study brings to light the importance of three types of formative feedback in problem or project-based learning. It offers two conceptual frameworks for instructional designers and curriculum developers. The models could be used to provide all forms of feedback including feed up, feedback and feed-forward to support student success in PBL learning environments.